2015
DOI: 10.3390/molecules201018201
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel Heterocyclic and Schiff Base Derivatives as Antimicrobial Agents

Abstract: Treatment of 2,3-diaryloxirane-2,3-dicarbonitriles 1a-c with different nitrogen nucleophiles, e.g., hydrazine, methyl hydrazine, phenyl hydrazine, hydroxylamine, thiosemicarbazide, and/or 2-amino-5-phenyl-1,3,4-thiadiazole, afforded pyrazole, isoxazole, pyrrolotriazine, imidazolothiadiazole derivatives 2-5, respectively. Reacting pyrazoles 2a-c with aromatic aldehydes and/or methyl glycinate produced Schiff's bases 7a-d and pyrazolo[3,4-b]-pyrazinone derivative 8, respectively. Treating 7 with ammonium acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 21 publications
(20 reference statements)
0
33
0
1
Order By: Relevance
“…Reaction of 3‐amino‐5,5‐(4‐tolyl)‐1 H ‐pyrazol‐4(5 H )‐ones (89) with methyl glycinate in boiling ethanol furnished 3,3‐di(4‐tolyl)‐2,3‐dihydro‐ 1H ‐pyrazolo[4,3‐ b ]pyrazin‐6( 7H )‐one (90) (Scheme ) .…”
Section: Synthesis Of Pyrazolo[34‐b]pyrazine Starting With Pyrazole mentioning
confidence: 99%
“…Reaction of 3‐amino‐5,5‐(4‐tolyl)‐1 H ‐pyrazol‐4(5 H )‐ones (89) with methyl glycinate in boiling ethanol furnished 3,3‐di(4‐tolyl)‐2,3‐dihydro‐ 1H ‐pyrazolo[4,3‐ b ]pyrazin‐6( 7H )‐one (90) (Scheme ) .…”
Section: Synthesis Of Pyrazolo[34‐b]pyrazine Starting With Pyrazole mentioning
confidence: 99%
“…The different kinds of electrophilic center in 2,3‐diaryloxirane‐2,3‐dicarbonitrile 1 are allowed to react with simply bi‐nucleophiles to afford the new heterocyclic compounds; they are dependent upon the type of nucleophile. 2,3‐Diaryloxirane‐2,3‐dicarbonitrile 1 is allowed to react with hydrazine precursors, such as hydrazine hydrate, methylhydrazine, and phenylhydrazine to afford the corresponding pyrazole derivative 2 that proposed the mechanism of pyrazole product 2 as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…From literature, it is found that the schiff bases derived from heterocyclic aldehydes such as furan-2-aldehyde, thiophene and pyridine-2-aldehyde can act as potential ligands and show considerable antibacterial activity [10][11][12][13] . The antibacterial property of the ligand P 2 CAAP and the complex [Ln(P 2 CAAP) (DMS)(NO 3 ) 3 ] were studied at different concentrations (0.01,0.02,0.03,0.04 and…”
Section: G Antibacterial Studymentioning
confidence: 99%